Penggunaan Kids Corner Dalam Sebuah Kegiatan Untuk Meningkatkan Interaksi Sosial Anak - Maria Riezqie Firnanda; Marina Wardaya (Universitas Ciputra Surabaya, 2019)
The purpose of this research is to find out the use of kids corner in Surabaya and Sidoarjo in an activity that can increase children's social interaction. The research method used in this research are qualitative and quantitative research methods. Qualitative data research methods by interviewing informants and users of kids corner services (expert users and extreme users) as well as literature studies from books and scientific journals about the use of gadgets on early childhood, the effect of gadgets on children's social interactions and the use of kids services corner in an activity. Quantitative research methods by distributing online and offline questionnaires to 52 potential customers in Surabaya and Sidoarjo. The conclusion of this research is the need for the use of kids corner in an activity to increase children's social interaction and minimize the use of gadgets to children.